Cephalic version by postural management in the lateral position without the knee‐chest position for primiparous breech presentation: A retrospective cohort study. Issue 3 (6th January 2022) - Shinmura, Hiroki; Matsushima, Takashi; Okuda, Naofumi; Watanabe, Asako; Nagashima, Asako; Yamada, Mayu; Harigane, Eika; Tsunoda, Youhei; Ichikawa, Go; Suzuki, Shunji
Abstract: Aim: This study aimed to determine the efficacy of postural management in the lateral position for primiparous breech presentation. Methods: A retrospective cohort study was conducted at a single institution from January 2020 through December 2020. Participants were singleton primiparous pregnant women diagnosed with breech presentation between 28 + 0 and 29 + 6 weeks of gestation. The exclusion criteria were scheduled cesarean delivery, uterine malformation, transverse position, and scheduled delivery at another hospital. A doctor instructed the women in the intervention group to lie on their right sides several times a day if the fetal back was on the left side or lie on their left sides if the fetal back was on the right side. The knee‐chest position and other methods were not recommended. The control group received expectant management care. The primary endpoint was the percentage of fetuses in a cephalic presentation 2 weeks later. Results: Of the 56 women included in the study, 17 women were instructed to lie in the lateral position, and 39 women received expectant management care only. After 2 weeks, women who were instructed to lie in lateral position had a higher rate of fetal cephalic version than the control group (82.4% [14/17] vs. 43.6% [17/39], p = 0.017). No study participants experienced adverse effects. Conclusions: Two weeks of postural management in the lateral position without the knee‐chest position significantly reduced the rate of primiparous breech presentation in the third trimester of pregnancy.